P‐6.6: Fabrication of Cu BCE‐structure IGZO TFTs for 85‐inch 8K4K 120Hz GOA LCD Display. (28th November 2018) - Wang, Xiao; Ge, Shi-Min; Li, Shan; Jiang, M; Meng, Yan-Hong; Wu, Wei; Zhu, Feng; Li, Gong-Tan; Liu, Jing-Jing; Shi, Long-Qiang; Zhao, Feng; Park, D; et al.
Abstract : The electrical characteristics of the back‐channel‐etch (BCE) configuration based amorphous indium–gallium–zinc oxide (a‐IGZO) thin‐film transistors (TFTs) were studied. The passivation layer, the selection of color filter material and design of GOA TFT structure were modified for lessening the influence of H2O molecules adsorbing on the back channel of the BCE‐structure. The negative and positive bias temperature stress results revealed that the optimized GOA TFTs exhibited good device reliability. Finally, a high performance 85‐inch 8K4K 120Hz GOA LCD was demonstrated.